La société multiculturelle selon Jürgen Habermas (II) - Denis Goeldel (Recherches Germaniques)
Habermas’s polemic with the neo-conservative intellectuals over their denial of “universal human rights”, and his debate on “Asian values” and “Western values” with the governments of the South-West Asian state since the Vienna Conference (1993) are of fundamental importance to Habermas’s conception of multiculturalism. In these debates (1995-1997) he changes his attitude towards “non-Western cultures”. He turns away from the “ethno-centric view”, according to which, there is a late or delayed appropriation of the “Lumières” among non-Western cultures compared to the West. Habermas now seems to join a certain cultural relativism and advocates for a “unification” with non-Western – “Arab-Muslim” cultures. These should therefore find “equivalents” to western-made inventions, so-called “alternative forms of modernity” paving the way for an intercultural version of the “multiple modernities” concept. This is the latest version of his multiculturalism.